Rasetsu - Shiomi, Chika; Watabe, Kinami (San Francisco, CA : Viz Media, 2009)
"Rasetsu Hyuga works for an exorcist agency where she uses her special powers to banish evil spirits. There's a story behind the red flower mark on her chest though - it's a momento left by a power spirit who vowed to claim her on her 20th birthday. Unless Rasetsu can find true love by then, she is fated to become his.--"P. [4] of cover, v.1.
Manga style.
Originally published in Japan in 2006 by Hakusensha, Inc., Tokyo.
Translated from Japanese.
Keywords: Exorcism; Fantasy comic books, strips, etc; Fantasy -- Comic books, strips, etc; Exorcisms -- Fiction; Graphic novels; Manga; Comics (Graphic works); Comic books, strips, etc; Comic books, strips, etc; Comics (Graphic works)